Treatment of Coloured Textile Wastewater by Activated Clay - Bouabdesselam, H.; Meddah, S.; Bouzidi, Y.; Bourg, D. (Asian Journal of Chemistry, 2016)
Activated clay has been successfully applied for the removal of red dye H3BD in the industrial textile wastewater. Activated clay has proved its effectiveness as 98% of the dyes contained within the effluent are eliminated and the COD is reduced from 10800 ppm to 32 ppm with a neutral pH and an excellent decantability. A complete study of textile dye adsorption on acidified clay was performed changing several factors such as stirring velocity, contact time and initial concentration.